Is there a paradox of a Hayekian paternalist? - Michael Wohlgemuth (Max Planck Institute of Economics, 2011)
Is Friedrich von Hayek in some specific, perhaps paradoxical, way a classical liberal paternalist? My answer will be an unsatisfying yes and no depending not only on my interpretation of Hayek, but also on the manifold interpretations one can give to the concepts of paternalism and classical liberalism (or, indeed: liberty). I start with an interpretation of Hayek's account of modernity. Here, I hint at a first potential paradox in the form of a magic triangle composed of (a) Hayek's praise and explanation of the evolutionary emergence of the spontaneous order of the market and civil society, (b) Hayek's fierce opposition to modernist thinking and the fatal conceit of rationalist constructivism and (c) Hayek's gloomy visions of politics, legislation, or public choice. Next, I shortly distinguish various dimensions of paternalism and confront these with Hayek's classical liberalism. In the following parts, I offer a brief account of behavioral anomalies of public choices that are analogous to, and even more harmful than, those used as legitimizations of libertarian paternalism in the private realm. I end up with a qualified claim that at least in the realm of potentially self-damaging collective choices, Hayek might be called a (classical liberal) paternalist.
Keywords: 330; Soziale Wohlfahrtsfunktion; Meritorisches Gut; Wirtschaftsliberalismus; Verfassungsökonomik; Theorie